Analisis Strategi Pada UMKM Samosa Mubels Menggunakan Model Strategi Framework 7S - Andrea Putri, Gigi Nurul (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This article aims to analyze the application of elements in the McKinsey 7S Framework in the operations of umkm Samosa Mubels, with a focus on the alignment between vision, organizational structure, marketing system and team performance. Through a qualitative approach with interviews with business owners, this article also evaluates the effectiveness of the marketing strategies implemented and identifies innovation opportunities to strengthen market position. UMKM Samosa Mubels is a culinary business that specializes in samosa products and typical Acehnese iced tea. To achieve its goal, namely advancing MSMEs in Meulaboh and introducing the culinary flavors of Aceh to tourists, Samosa Mubels implements various marketing strategies and product innovations.